Enhancing PEPT: high fidelity analysis techniques with augmented detection systems - Van Der Merwe, Robert (Department of Physics, 2025)
Positron emission particle tracking (PEPT) is a non-invasive, tracer-based technique used in the study of dynamic systems, such as particulate and fluid flows. Relying on positron imaging principles, typical PEPT systems operate with millimetre precision at tracking speeds of up to 10 m/s, with applications in fields from engineering to medicine. Performance is constrained by the efficiency of conventional fixed geometry detector systems and achievable activity of tracer particles, creating challenges when addressing phenomena on the micro-scale. Previous work with a pair of pixelated cadmium zinc telluride (CZT) room temperature semiconductors (9680 pixels of 1.8 x 1.8 x 0.5 mm3) exhibited potential in micro-scale PEPT, but achievable location rates and field of view (FOV) were limiting. To address these issues, a modular bismuth germanate oxide (BGO) scintillator array, consisting of 1024 detector elements (512 pixels of 6.75 x 6.25 x 30 mm3 and 512 pixels of 4.1 x 4.0 x 30 mm3), has been developed and characterised for use in a hybrid system, combining semiconductor and scintillator de vices. Optimal detection system geometry was determined through numerical modelling of system sensitivity, with the BGO array covering a FOV of 120×174×102 mm3 and the high-resolution semiconductor FOV of 62 × 42 × 20 mm3 placed centrally. This design maximises absolute efficiency through the scintillators and spatial resolution through the semiconductors. A coincidence timing resolution of 5.37 ± 0.17 ns and an energy resolution of 30.51 ± 0.48% at 511 keV was measured for the BGO devices, enabling optimisation of coincidence gates and energy level discriminators respectively. Using a novel 3D positioning stage and a 20.11 ± 0.26 kBq Na-22 calibration source, measurements of system sensitivity, spatial resolution and accuracy were performed. Sensitivity profiles were found in agreement with simulation, with a maximal central sensitivity of 34.8 ± 0.6 cps/kBq. Sub-millimetre system accuracy was achieved in all axes except between the BGO detector faces, in which an expected warping effect was identified. Sub-millimetre spatial resolution, σ, was achieved for a maximum location rate per unit activity, L ′, of 0.45 Hz/kBq, with an identified σ = 1.5 √ L′ trade-off to be optimised for specific use cases. The results of this work demonstrate the applicability of PEPT to the study of micro-scale phenomena and outline the path towards hybrid implementation